Cerebral perfusion pressure and behavior monitoring in freely moving rats - Kozler, P; Marešová, D; Hrachovina, M; Pokorný, J (Physiological research, 2023)
Cerebral perfusion pressure (CPP) is the net pressure gradient that drives oxygen delivery to cerebral tissue. It is the difference between the mean arterial pressure (MAP) and the intracranial pressure (ICP). As CPP is a calculated value, MAP and ICP must be measured simultaneously. In research models, anesthetized and acute monitoring is incapable of providing a realistic picture of the relationship between ICP and MAP under physiological and/or pathophysiological conditions. For long-term monitoring of both pressures, the principle of telemetry can be used. The aim of this study was to map changes in CPP and spontaneous behavior using continuous pressure monitoring and video recording for 7 days under physiological conditions (group C - 8 intact rats) and under altered brain microenvironment induced by brain edema (group WI - 8 rats after water intoxication) and neuroprotection with methylprednisolone - MP (group WI+MP - 8 rats with MP 100 mg/kg b.w. applicated intraperitoneally during WI). The mean CPP values in all three groups were in the range of 40-60 mm Hg. For each group of rats, the percentage of time that the rats spent during the 7 days in movement pattern A (standard movement stereotype) or B (atypical movement) was defined. Even at very low CPP values, the standard movement stereotype (A) clearly dominated over the atypical movement (B) in all rats. There was no significant difference between control and experimental groups. Chronic CPP values with correlated behavioral type may possibly answer the question of whether there is a specific, universal, optimal CPP at all.
Keywords: mozkový krevní oběh; Intracranial Pressure; Cerebrovascular Circulation; Brain; intrakraniální tlak; Rats; zvířata; mozek; monitorování fyziologických funkcí; Blood Pressure; telemetrie; krevní tlak; Monitoring, Physiologic; Telemetry; krysa rodu Rattus; Animals